2002
DOI: 10.1183/09031936.02.00301502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of terbutaline in combination with mannitol on mucociliary clearance

Abstract: b 2 -agonists and osmotic agents stimulate mucociliary clearance (MCC) via different mechanisms which could potentially interact.The effects of inhaling terbutaline in combination with mannitol on MCC were investigated in nine healthy (aged 19¡1 yrs) and 11 mild (aged 21¡4 yrs) asthmatic subjects. Using 99m Tc-sulphur colloid radioaerosol and a gamma camera, MCC was studied on four separate days with each of the following interventions: 1) terbutaline or its placebo inhaled 10 min before mannitol (in random, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Since vascular engorgement and edema in response to hyperpnea are thought to exaggerate airway obstruction in EIB ( 3 ), the antiexudative action of β 2 -adrenoceptor agonists may have contributed to bronchoprotection in our study. Furthermore, there is a possibility that the β 2 -adrenoceptor agonist may have limited excessive and viscous mucosal accumulation by increasing cilia beat frequency ( 23 ) and improving clearance of alveolar ( 51 ) and/or mucociliary fluids ( 21 , 41 ). Finally, the β 2 -adrenoceptor agonist may have preserved/improved airway caliber due to its well-known effect on airway smooth muscle tone.…”
Section: Discussionmentioning
confidence: 99%
“…Since vascular engorgement and edema in response to hyperpnea are thought to exaggerate airway obstruction in EIB ( 3 ), the antiexudative action of β 2 -adrenoceptor agonists may have contributed to bronchoprotection in our study. Furthermore, there is a possibility that the β 2 -adrenoceptor agonist may have limited excessive and viscous mucosal accumulation by increasing cilia beat frequency ( 23 ) and improving clearance of alveolar ( 51 ) and/or mucociliary fluids ( 21 , 41 ). Finally, the β 2 -adrenoceptor agonist may have preserved/improved airway caliber due to its well-known effect on airway smooth muscle tone.…”
Section: Discussionmentioning
confidence: 99%
“…This is in good agreement with previous studies by Devalia et al and Yaghi et al (18,33), which also found a significant enhancement of CBF following SS and MA exposure to bronchial epithelial cells. The increase in the CBF by both drugs may be mediated via the β 2 adrenergic pathway, leading to the release in cAMP and increase in intracellular calcium in response to hyperosmolar stimuli, respectively (34). Although CBF was augmented when the drugs were given in combination, no significant difference was found between the treatment groups (i.e.…”
Section: Ciliary Activitymentioning
confidence: 95%
“…Patients inhaled 99m Tc‐labelled sulphur colloid particles and the rate of clearance of these particles from the lung was then determined using a gamma camera. We have found that the rate of clearance of particles is increased following administration of the β‐adrenoceptor agonist terbutaline, providing indirect evidence that the increase in cilial beat frequency is also demonstrable in vivo in subjects with asthma 8 …”
Section: Exercise‐induced Asthmamentioning
confidence: 76%
“…We have found that the rate of clearance of particles is increased following administration of the ␤ -adrenoceptor agonist terbutaline, providing indirect evidence that the increase in cilial beat frequency is also demonstrable in vivo in subjects with asthma. 8 In recent years, it has become evident that the stimulus for EIA is hyperosmolarity of the respiratory mucosa, as a consequence of water loss during hyperventilation of exercise. 9 This hyperosmolarity of the mucosa, which activates the mast cells to release their mediators, can be mimicked by the inhalation of the osmotic agent mannitol.…”
Section: Exercise-induced Asthmamentioning
confidence: 99%